TRADISI SAPARAN DALAM BUDAYA MASYARAKAT JAWA DI LUMAJANG - Tutuk Ningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
Indonesia has diverse tribes and traditions that make Indonesia rich of various cultures. As an ancestral heritage, cultural traditions are still preserved by Indonesian society. There are some traditions that arecarried out every year, as well as by Javanese who continue to enforce their cultural traditions, because it relates to their religion and does not harm the society. This study aims to describe and analyze Saparan Tradition of Javanese society. This research implements qualitative research method, with the data is obtained directly from the field through observation at the actual conditions in the society, among Moslem Javanese.The data collections in this study are observation, documentation and interview. The results of the study related to the socio-cultural and religious conditions of Ditotrunan society. They are unique. Geographically,their location is in the center of the city, but still holding the tradition of saparan every year. The tradition on Safar Month, which is known as saparan by the Javanese in Lumajang, is carried out by making jenang asan expression of gratitude or slametan. Each family makes jenang in Safar Month, they take turns to make jenang, and then it is served in a leafcoated plate. After everything is ready, it will be presented on the table.Then, the head of the household leads a prayer for goodness, then sharing jenang to the neighbors and the relatives next to them. In addition, in saparan tradition, there is also a festival followed by ladies dressed inkebaya (Javanese Blouse), they work together to make jenang. After cooking, they place the meal on a grounded leaf plate. Then, a prayer is conducted and led by the priest. Finally, they eat jenang together in thesociety.